Toxicity of Extract Tobacco Leaves to The growth of Oreochromis niloticus - Siti Rudiyanti (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2010)
Tobacco can be used as natural pesticide since it contained high concentration of nicotine that may killed pest and fish diseases. This work aimed to know the influence and inhibiting concentration of tobacco leaves extract to the growth of Tilapia. The research was conducted on March to May 2007 at laboratory of Satker PBIAT Ngrajek, Magelang. Fish fry used were in between 1,74±0,105 g with the density of 10 were tested in 20 L fresh water, were tested using several concentration of tobacco leaves extract. Sub lethal toxicity tested in the laboratory using complete random design for 28 days. The result showed that LC50 -96 hours is 22,492 mg/L. It is shown that extract of tobacco leaves has a significant influence to the fish growth. The highest absolute biomass growth is at treatment  K (3,72 g), followed by treatment  A (3,29 g), B (2,96 g), C (2,75 g), and D (2,24 g). Whereas the highest daily growth rate is also at treatment K (3,93 %), followed by A (3,75 %), B (3,59  %), C (3,45 %), and D (3,06 %). The inhibiting concentration (IC 50) is 15,733 mg/L. Water quality during the experiment indicated a suitable condition for fish life medium.                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                          Key Words : Extract of tobacco leaves, Tilapia fry, Growth